Hao-Fountain syndrome: 32 novel patients reveal new insights into the clinical spectrum - Wimmer, Moritz Claudius; Brennenstuhl, Heiko; Hirsch, Steffen; Dötsch, Laura; Unser, Samy; Caro, Pilar; Schaaf, Christian P. (Clinical genetics, 2024)
Hao-Fountain syndrome (HAFOUS, OMIM: #616863) is a neurodevelopmental disorder caused by pathogenic variants in the gene USP7 coding for USP7, a protein involved in several crucial cellular homeostatic mechanisms and the recently described MUST complex. The phenotype of HAFOUS is insufficiently understood, yet there is a great need to better understand the spectrum of disease, genotype-phenotype correlations, and disease trajectories. We now present a larger cohort of 32 additional individuals and provide further clinical information about six previously reported individuals. A questionnaire-based study was performed to characterize the phenotype of Hao-Fountain syndrome more clearly, to highlight new traits, and to better distinguish the disease from related neurodevelopmental disorders. In addition to confirming previously described features, we report hyperphagia and increased body weight in a subset of individuals. HAFOUS patients present an increased rate of birth complications, congenital anomalies, and abnormal pain thresholds. Speech impairment emerges as a potential hallmark of Hao-Fountain syndrome. Cognitive testing reports reveal borderline intellectual functioning on average, although some individuals score in the range of intellectual disability. Finally, we created a syndrome-specific severity score. This score neither indicates a sex- nor age-specific difference of clinical severity, yet highlights a more severe outcome when amino acid changes colocalize to the catalytic domain of the USP7 protein.